New Models to Reduce the Health Risks of Informal WEEE Recyclers in MTN Phone Village, Rumukurushi, Port Harcourt, Nigeria - Ogechukwu Okwu; Andrew Hursthouse; Evi Viza; Linus Idoko (Toxics, 2022)
Waste electrical and electronic equipment (WEEE) management in Port Harcourt, an oil-producing city in Nigeria, has become an environmental challenge for the location. WEEE recycling is predominantly managed by informal recyclers, who lack the skills to perform risk-free recycling, hence raising health risks to individuals in associated communities and degrading the environment. Formal recycling, which embraces the best practices for effective WEEE management, is faced with several limitations, such as a lack of detailed guidelines on waste recycling, reuse, and final disposal techniques, with no opportunities for landfilling. A qualitative approach was adopted for this study. Data were gathered via questionnaires and analysed graphically. A background literature review of the assessment of informal recycling methods and associated challenges was performed. Hence, a new concept for the local management of WEEE processing was introduced. This concept limits the role of informal recyclers to WEEE collection. In this case, informal recyclers are paid for WEEE collection; they no longer engage in further WEEE processing. The results show that 48% and 40% agree to partner and collaborate with government agencies, respectively. Conversely, 52% and 40% agree and strongly agree, respectively, to limit their activities to WEEE collection only if the government is willing to pay for the services.